Comparison of push-out bond strength of furcation perforation repair materials - Glass ionomer cement Type II, hydroxyapatite, mineral trioxide aggregate, and biodentine: An in vitro study - Metashi Singla; Kanika Gupta Verma; Virinder Goyal; Purshottam Jusuja; Ashish Kakkar; Lovejeet Ahuja (Wolters Kluwer Medknow Publications, 2018)
Background: A furcation perforation is mid-curvature opening into periodontal ligament space which is a worst possible outcome in root canal treatment. Perforations should immediately be repaired with a biocompatible material to seal the communication between perforation site and gingival sulcus. Aim: The aim of this study was to evaluate the push-out bond strength of glass ionomer cement, hydroxyapatite, mineral trioxide aggregate, and biodentine (BD) when used in repairing furcal perforations with and without blood contamination in permanent molars. Materials and Methods: A total of 120 human extracted molars were collected and divided on the basis of perforation repair materials and blood contamination status (n = 15). All the materials were subjected to universal testing machine to a load cell from 0 N to 100 KN at a crosshead speed of 1 mm/min. Statistical Analysis: The data obtained were subjected to statistical analysis using SPSS version 20.0. Results and Conclusion: The push-out bond strength was maximum in BD contaminated with blood and least for the hydroxyapatite contaminated with blood. A significant difference was found between all the perforation repair materials.